FLOOD RISK IMPACT OF SPATIAL DEVELOPMENTS, CLIMATE CHANGE AND SUBSIDENCE: CASE STUDY IN THE NETHERLANDS - O. A. C. Hoes (Lowland Technology International, 2007)
Polder areas are vulnerable for inundations by extreme precipitation, as runoff may temporarily exceed the limited discharge capacity of drainage canals and pumping stations. This type of flooding is not life threatening, but can cause considerable economic damage. Furthermore, it is likely that frequency and damage of this type of flood events will increase in the future. The research question addressed in this paper is whether there is any need to improve water systems with respect to climate change, subsidence and spatial developments. To answer this question the case of the Flevo polder was studied. It will be shown that the risk increase of spatial developments, subsidence and climatechange simultaneously is larger then the sum of the individual risk increase per category.